An international stadium a study on the opening ceremony of the London 2012 Olympic games and cultural globalization - Gatpandan, Nathaniel Christian A. 1992- (2013)
"This study focuses on the opening ceremony of the Olympic Games of London 2012. It examines and analyzes the Bristish Broadcasting Corporation (BBC) live broadcast of the ceremony as a cultural artifact using Benedict Anderson in 'Imagined Communities'. Beyond the text, different aspects of the globalization of the Olympics through media were also explored through the writings of several Olympic scholars. Before the events if the Olympic Games commence, an extravagant opening ceremony is held, organized by the government of the host nation, and its private partners. The Olympic Stadium is turned into a tableau where the host paints an image of itself to be seen all across the globe. This study extracted projected elements of British national identity and organized under seven categories of the British branding to discover the ways that the London Olympic Games Organizing Committee used the ceremony as an identity-building mechanism for the United Kingdom. This research discovered that the London 2012 Olympic Opening Ceremony can be viewed as a history book, a portcard, among other things, and was an opportunity for the British government to shift perspectives of backwardness on their nation, but instead, the ceremony was conventional and more nostalgic. It even branded itself as "highly British" (BBC,2012). These forms of their national identity reinforce the simultaneity of movements of individual members of the British nation, and eventually, the imagining of the British brand through the segments of the ceremony."